General practitioner referrals to an eye hospital: a standard referral form. - Jones, N P (1990)
To assess general practitioner (GP) referrals to an eye hospital, 500 consecutive referral letters were analysed for content, diagnosis, ocular examination, and medical and drug history. Inadequate information was provided. Visual acuity was measured by general practitioners in only 3.7% of referrals. The standard of ocular examination compared unfavourably with that of ophthalmic opticians. A standard ophthalmic referral form is proposed, and referral protocols are desirable. Undergraduate education in ophthalmology is inadequate and requires more curricular time.